ELIMINATING PSYCHOLOGICAL ABUSE THAT OCCURS IN WOMEN DURING CLIMAX - Ataxanova.Lobar. Egamberganovna (Web of Journals Publishing, 2024)
This article provides opinions on the period of climax, its main signs, characteristics, effects on women's health, results and psychological conditions and factors that help in their elimination.
Keywords: climax, egg cell, follicle, menopause, norm, physiology, depression.